Strategi Komunitas Intellectual Publik - Amin Silalahi (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2010)
Strategies intellectual community realized the public is very important today because the public must have the intellectual community characteristics and concrete contribution towards the public issue to find the truth about the (God, Science and Moral) through the ideas contained in: research, teaching and community service through a multi-disciplinary science. Third public spaces that include: research, teaching and community service for the community to give space for the public intellectual exchange between the intellectual mind of the will and collective interests, and seek kebenaran humanity and justice. Interaction between vision / mission and goals of the public intellectual community must be adapted to the environmental issues of public and environmental science specialist from Widya Mandala Surabaya UNIKA so that strategic decisions are tailored to the resources, structure, culture, policies, programs and budget and should be evaluated and controlled so that the universal values of public properties of precedence with a comprehensive, integrated and unified in the mind-heart-will in order to create a man for Others and Improving Life University is mainly intended for the weak groups in society.